2015
DOI: 10.1109/led.2015.2478899
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Contact Analysis of Multilayer MoS<sub>2</sub> Transistor With Molybdenum Source/Drain Electrodes

Abstract: We demonstrate two-dimensional (2D) multilayered molybdenum disulfide (MoS2) transistor with molybdenum (Mo) side and edge contacts, which is deposited by using DC-sputtering method. It exhibits field-effect mobility of 23.9 cm 2 /Vs and on/off ratio of 10 6 in a linear region. Current-voltage study under different temperatures (300-393 K) reveals that Mo-MoS2 transistor shows a band transport characteristics, and a Schottky barrier height of 0.14 eV is estimated using thermionic emission theory. Finally, side… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…They found that the electrical performance of their 96-layer or 67 nm thick MoS 2 FET (µ FE~2 4 cm 2 /V-s) was similar to few-layer (3-5L) MoS 2 FETs with Mo top contacts (µ FE~2 6-27 cm 2 /V-s). This clearly suggests that the detrimental effect of R int was greatly minimized even though the MoS 2 was 67 layers thick, thanks to the formation of edge contacts (due to conformal Mo deposition by DC-sputtering) that injected carriers deep into the constituent layers of the multilayer MoS 2 device [278]. Chai et al developed a "passivation first, metallization second" technique for fabricating pure edge contacts to two types of back-gated MoS 2 -based heterostructures wherein the MoS 2 was first encapsulated in-between dielectrics: Al 2 O 3 /MoS 2 /SiO 2 and hBN/MoS 2 /hBN.…”
Section: Effects Of Contact Architecture (Top Versus Edge)mentioning
confidence: 99%
“…They found that the electrical performance of their 96-layer or 67 nm thick MoS 2 FET (µ FE~2 4 cm 2 /V-s) was similar to few-layer (3-5L) MoS 2 FETs with Mo top contacts (µ FE~2 6-27 cm 2 /V-s). This clearly suggests that the detrimental effect of R int was greatly minimized even though the MoS 2 was 67 layers thick, thanks to the formation of edge contacts (due to conformal Mo deposition by DC-sputtering) that injected carriers deep into the constituent layers of the multilayer MoS 2 device [278]. Chai et al developed a "passivation first, metallization second" technique for fabricating pure edge contacts to two types of back-gated MoS 2 -based heterostructures wherein the MoS 2 was first encapsulated in-between dielectrics: Al 2 O 3 /MoS 2 /SiO 2 and hBN/MoS 2 /hBN.…”
Section: Effects Of Contact Architecture (Top Versus Edge)mentioning
confidence: 99%
“…Contact resistance is one of the key factors attributing to the loss of mobility since the formation of a Schottky barrier for electron injection greatly limits the FETs performance . A number of past works have been conducted to improve the contact resistance recently . For example, phase engineered MoS 2 can greatly reduce the contact resistance while the metastable 1T phase MoS 2 limits its application .…”
mentioning
confidence: 99%
“…Most of the preparation and device application of MoS 2 were focused on ultra-thin films. However, a few previous reports of multilayer MoS 2 have suggested the potential for its device applications [7][8][9] since multilayer structure of MoS 2 is insensitive to the extrinsic factors [10] and enhances the current flow of FET [11].…”
Section: Introductionmentioning
confidence: 99%